Psychological analysis in long-term dialysis patients - Harada, Ryuji; Takayama, Iwao; Irisa, Soichi; Kato, Hisako; Hashimoto, Shuji; Terashi, Munekazu; Otsuji, Yoshihito (Jinko Toseki Kenkyukai kaishi. [Journal of the Dialysis Research Society, 1984)
The mumber of long-term dialysis patients nowadays has increased as the methods of dialysis treatment have progressed. In addition, the better prognosis of the patients is presumed to be closely related to self-management which is influenced by the psychological state of each patient. We have made an investigation mainly on those under dilaysis treatment for more than 10 years in respect of psychological analysis in order to clarify the psychological factors which may contribute to longer survival. Method: 1) Analysis, by interview, of the mental and psychological coures of a patient receiving dialysis treatment for 12 years and 7 months, who has made his way, overcoming some complications. 1) Analysis of 60 dialysis patients based on two methods of psychological testing, the Cornell medical index (CMI) and the self rating questionnaire for depression (SRQ-D). 3) Analysis of long-term dialysis patients using two psychological tests, the social adjustment scale (SAS) and the dialysis sentence completion test (D-SCT). Results: Mental and psychological analysis of the patients showed that: a) The patients turn greatly to encouragement by family members as well as spiritual support from religion. b) Complex psychological reactions are expressed toward complications that develop. c) Economical issues greatly concern the patients. d) The patients be come more competent and recover confidence as they survive longer. Further more, the results of the two psychological tests, CMI and SRQ-D, performed on the patients suggest that there were fewer neuropathic and/or depressive tendencies among longer surviving dialysis patients. It has also been shown, as a result of psychological tests based on SAS and D-SCT, that longer surviving dialysis patients were known to be more adjustable in their own communities before the onset of the disease and, thereafter, adapted themselves well to the dialysis treatment.